Temperature-controlled selectivity in oxidation of 1-octene by using aqueous hydrogen peroxide in phase-boundary catalytic system - Lai, Sin Yuan (2013)
Temperature-controlled selectivity in oxidation of 1-octene by using aqueous hydrogen peroxide in phase-boundary catalytic system was demonstrated by using alkylsilylated-Ti(IV) salicylaldimine complex at a series of temperature (25–90 °C). The catalyst was synthesized by titanium(IV) sulfate solution, salicylaldehyde, and 3-aminopropyltrimethoxysilane as the precursors and followed by the attachment of octadecyltrimethoxysilane. It was found that the reaction system resulted in high selectivity at low temperature. One suggests that the high selectivity in the oxidation of 1-octene by aqueous hydrogen peroxide was related to partitioning of alkylsilylated-titanium(IV) salicylaldimine complex in immiscible liquid–liquid phase boundary which is temperature dependent.